2014
DOI: 10.1080/02640414.2014.990489
|View full text |Cite|
|
Sign up to set email alerts
|

Confounding compression: the effects of posture, sizing and garment type on measured interface pressure in sports compression clothing

Abstract: The purpose of this investigation was to measure the interface pressure exerted by lower body sports compression garments, in order to assess the effect of garment type, size and posture in athletes. Twelve national-level boxers were fitted with sports compression garments (tights and leggings), each in three different sizes (undersized, recommended size and oversized). Interface pressure was assessed across six landmarks on the lower limb (ranging from medial malleolus to upper thigh) as athletes assumed sitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 22 publications
1
30
2
1
Order By: Relevance
“…Exercise that is unaccustomed or unfamiliar in nature can lead to the experience of exerciseinduced muscle damage (EIMD) (1,2). Symptoms associated with EIMD include decreased force production, decreased range of motion (ROM) and the experience of muscle soreness, all of which can negatively affect performance (3).…”
Section: Introductionmentioning
confidence: 99%
“…Exercise that is unaccustomed or unfamiliar in nature can lead to the experience of exerciseinduced muscle damage (EIMD) (1,2). Symptoms associated with EIMD include decreased force production, decreased range of motion (ROM) and the experience of muscle soreness, all of which can negatively affect performance (3).…”
Section: Introductionmentioning
confidence: 99%
“…A number of primary studies have demonstrated that physiological effects vary according to the pressure applied (Miyamoto et al, 2011;Coza et al, 2012;Bochman et al, 2005). In addition, a number of studies have demonstrated that pressure applied is hard to predict from sizing and varies with changes in posture and activity (Brophy-Williams et al, 2015;Hill et al, 2015;de Godoy et al 2010). Measuring pressure between the garment and the body is recommended to describe such interventions clearly.…”
Section: Discussion Of Main Findingsmentioning
confidence: 99%
“…Based on these observations, it seems questionable whether it would be useful at all for SCS to comply with MCS standards. In sports, even footless compression garments such as leggings or inelastic calf wraps have been shown to be effective . It would seem more adequate to develop a separate classification for sport compression garments, which would enable athletes to select appropriate products based on preference, target parameters, and type of sport.…”
Section: Discussionmentioning
confidence: 99%